2020
DOI: 10.1016/j.isci.2020.101119
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of β2m Molecule-Induced Changes in the Peptide Presentation Profile in a Bony Fish

Abstract: Two Ctid-b2ms loci with distinct polymorphic features are found in a bony fish The pMHC-I complexes peptide-binding profiles exhibit different characteristics The crystal structures of pCtid-UAA-b2m-2/1-II complexes are determined The structural mechanism changing the peptide presentation profile is proposed DATA AND CODE AVAILABILITY 6LBE 5H5Z

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Moreover, the inclusion of probiotics has been evaluated through the immune system gene expression such as interleukins, where Il-10 stands out, which is an immunosuppressive cytokine that prevents immune-mediated damage to the host by dampening inflammatory responses of the immune response (Howes et al 2014), the β2 microglobulin (b2m) is classified as part of the set of the immunoglobulin superfamily (IgSF) and play important roles in the adaptive immune system (Chen et al 2010). The immunological function of b2m is to assist classical major histocompatibility complex (MHC) class I (i.e., MHC-I) molecules in assembling endogenous antigen peptides, forming a trimolecular complex (i.e., pM-HC-I) and then presenting them to the surface of antigen-presenting cells (APCs); through interaction with T cell receptors (TCRs), specific cytotoxic T lymphocyte (CTL) immunity is thus induced (Flajnik and Kasahara 2001;Li et al 2020), and the transforming growth factor β1 (tgf-β1), which is an important multifunctional cytokine involved in the regulation of cell proliferation, differentiation, survival, migration, and apoptosis under physiological and pathological conditions (Qi et al 2016). For example, tgf-β1 acts as an immunosuppressive mediator and inhibits nitric oxide production in TNF-γ-activated macrophages in fish (Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the inclusion of probiotics has been evaluated through the immune system gene expression such as interleukins, where Il-10 stands out, which is an immunosuppressive cytokine that prevents immune-mediated damage to the host by dampening inflammatory responses of the immune response (Howes et al 2014), the β2 microglobulin (b2m) is classified as part of the set of the immunoglobulin superfamily (IgSF) and play important roles in the adaptive immune system (Chen et al 2010). The immunological function of b2m is to assist classical major histocompatibility complex (MHC) class I (i.e., MHC-I) molecules in assembling endogenous antigen peptides, forming a trimolecular complex (i.e., pM-HC-I) and then presenting them to the surface of antigen-presenting cells (APCs); through interaction with T cell receptors (TCRs), specific cytotoxic T lymphocyte (CTL) immunity is thus induced (Flajnik and Kasahara 2001;Li et al 2020), and the transforming growth factor β1 (tgf-β1), which is an important multifunctional cytokine involved in the regulation of cell proliferation, differentiation, survival, migration, and apoptosis under physiological and pathological conditions (Qi et al 2016). For example, tgf-β1 acts as an immunosuppressive mediator and inhibits nitric oxide production in TNF-γ-activated macrophages in fish (Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are indications for the involvement of b 2 -m in "tuning" the peptide binding groove-rather than being a simple "lock" for the pMHC-I complex-as, for example, shown by a recent study of our group in carp. Namely, in two carp pMHC-I structures with identical HC and peptide, but with different, naturally occurring, paralogous b 2m variants, the peptide was bound in a different conformation (58). This finding in carp was not unexpected, since earlier reports had found that naturally occurring allelic variation in mouse b 2 -m is associated with differences in peptides presented by MHC-I (91) and T cell stimulation (91,92).…”
Section: Discussionmentioning
confidence: 82%
“…With the elucidation of shark pUAA, pMHC-I structures are now known for a variety of placental mammals (36,51,53), including chickens and ducks (5456), the amphibian African clawed frog (57), the bony fish grass carp (41,58), and the nurse shark (Fig. 2Ba).…”
Section: Resultsmentioning
confidence: 99%
“…Structures of pMHC-I have now been determined throughout the major clades of jawed vertebrates including cartilaginous fish (27), bony fish (28,29), amphibians (30), the birds chicken [e.g., (31)(32)(33)] and duck (34), and a variety of mammals [e.g., (4,(35)(36)(37)(38)], whereas pMHC-II structures only have been determined for chicken (39), mouse [e.g., (40)], and human [e.g., (5)]; most of the here listed studies in primitive vertebrates were performed by our group. This recent accumulation of MHC structural information across widely divergent species invites a deeper analysis of MHC evolution.…”
Section: Introductionmentioning
confidence: 99%